1995
DOI: 10.1021/jo00119a020
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Nonionic X-ray Contrast Agents. 4. The Synthesis of Dihydro-2(3H)-furanylidenamino, 5-oxo-1-pyrrolidinyl, and 5-oxo-4-morpholinyl Derivatives by an Intramolecular Iodocyclization Approach

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Additionally, multiple iodinated aromatic rings are fused together in order to reduce osmolality while maintaining high administered iodine content. Though several contrast agents (ionic, nonionic, and one/two aromatic ring structures) are approved for clinical use and produced worldwide, new contrast agents with high water solubility, low viscosity and osmolality, and reduced toxicity continue to be of interest. Contrast agents that go beyond qualitative visualization and enable quantitative assessments of functional tissue performance represent the next (third) generation of contrast agents. One clinical area where such contrast agents can have a significant impact is in the diagnosis of soft tissue-based diseases like osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, multiple iodinated aromatic rings are fused together in order to reduce osmolality while maintaining high administered iodine content. Though several contrast agents (ionic, nonionic, and one/two aromatic ring structures) are approved for clinical use and produced worldwide, new contrast agents with high water solubility, low viscosity and osmolality, and reduced toxicity continue to be of interest. Contrast agents that go beyond qualitative visualization and enable quantitative assessments of functional tissue performance represent the next (third) generation of contrast agents. One clinical area where such contrast agents can have a significant impact is in the diagnosis of soft tissue-based diseases like osteoarthritis (OA).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophilic Cyclization of Conjugated Unsaturated Amides 3 Leading to Cyclic Imino Ethers. It is known that the electrophilic cyclization reaction patterns of unsaturated amides remarkably depend on the reaction solvents and the electrophiles employed. For these cases of dienamides 3a − m , we found that the best conditions for the cyclization reaction were the use of 12 N HCl both as a electrophile and as a solvent at room temperature (Scheme ). Although the substitution patterns of the dienyl skeletons of 3a − k is different from that of 3l and 3m , all these dienamides, except 3l , underwent the same type of electrophilic cyclization.…”
Section: Resultsmentioning
confidence: 85%
“…In this paper, we report an alternative synthesis of these conjugated unsaturated amides 3 and their applications to the preparation of heterocycles via electrophilic cyclization. Surprisingly, our results reveal that these multisubstituted dienamides 3 undergo the electrophilic cyclization exclusively through the O -attack pathway to afford cyclic imino ethers, which are seldom obtained via the electrophilic cyclization. …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Preliminary studies toward intramolecular N -cyclization to form bicyclic lactam 14 were focused on an iodolactamization/elimination sequence (Scheme 4). Subjection of 11 to conditions precedented in the literature for regioselective N -cyclization afforded an 88:12 mixture of regioisomers favoring the desired, N -cyclized product 12 over the undesired O-cyclized product 13 . The crude mixture of 12 and 13 was treated with DBU in toluene, which cleanly formed the elimination products 14 and 15 .…”
Section: Resultsmentioning
confidence: 99%